A novel mode of enhancer evolution: The Tal1 stem cell enhancer recruited a MIR element to specifically boost its activity - Smith, Aileen M.; Sanchez, Maria-Jose; Follows, George A.; Kinston, Sarah; Donaldson, Ian J.; Green, Anthony R.; Göttgens, Berthold

(untitled) (Genome Research, 2008)
Altered cis-regulation is thought to underpin much of metazoan evolution, yet the underlying mechanisms remain largely obscure. The stem cell leukemia TAL1 (also known as SCL) transcription factor is essential for the normal development of blood stem cells and we have previously shown that the Tal1 +19 enhancer directs expression to hematopoietic stem cells, hematopoietic progenitors, and to endothelium. Here we demonstrate that an adjacent region 1 kb upstream (+18 element) is in an open chromatin configuration and carries active histone marks but does not function as an enhancer in transgenic mice. Instead, it boosts activity of the +19 enhancer both in stable transfection assays and during differentiation of embryonic stem (ES) cells carrying single-copy reporter constructs targeted to the Hprt locus. The +18 element contains a mammalian interspersed repeat (MIR) which is essential for the +18 function and which was transposed to the Tal1 locus ∼160 million years ago at the time of the mammalian/marsupial branchpoint. Our data demonstrate a previously unrecognized mechanism whereby enhancer activity is modulated by a transposon exerting a “booster” function which would go undetected by conventional transgenic approaches.